Bond behaviour degradation between FRP composites and brick masonry - Oliveira, Daniel V. (2017)
FEDER funds through the Competitivity Factors Operational Program - COMPETE and by national funds through FCT – Foundation for Science and Technology within the scope of project POCI-01-0145-FEDER-007633. The third author acknowledges the financial support of the Ministério da Ciência, Tecnologia e Ensino Superior, FCT, Portugal, under the grant SFRH/BPD/92614/2013